Broker based trust architecture for federated healthcare cloud system. Issue 3 (3rd July 2017) - Mohan, K.; Aramudhan, M.
Abstract: Cloud healthcare is the challenging, growing exponentially and heterogeneous technical environment involving various roles such as medical practitioners, pharmacists, patients and IT professionals to access the information through different technologies and types of devices. In this paper, federated healthcare cloud broker architecture is proposed where the independent health service providers can be integrated together to form a large healthcare federation, fulfill the requirements of users by sharing the available resources at different locations with affordable prices and provides Quality of Service (QoS) to all end users. Different trust mechanisms such as Policy based trust; SLA verification trust and reputation based trust are computed to ensure the security and privacy of the users, who accessing the services in the proposed architecture. Service Measurement Index (SMI) attributes suggested by the Cloud Service Index Measurement Consortium (CSIMC) used to calculate trust values of the health provider, based on the calculated trust value, the selection is proposed for the specific request that helps to improve the reliability, security and privacy. To resolve the strict treatment of the differentiated module, a new mechanism is suggested as Patient Turned Queuing Scheduling (PTQS) to resolve the possibility of starvation happening in the existing differentiated modules. Simulation results show that the performance of the proposed mechanism is better than the existing random provider and feedback based selection mechanism in the related works.